Supervising financial regulators - Josef Schroth (Bank of Canada, 2016)
How much discretion should local financial regulators in a banking union have in accommodating local credit demand? I analyze this question in an economy where local regulators privately observe expected output from high lending. They do not fully internalize default costs from high lending since deposit insurance cannot be priced fairly. Still, output net of default costs across the banking union is highest when local regulators are rewarded rather than punished. Regulators with lower current lending receive more discretion to allow higher lending in the future, but regulators with higher current lending may not experience any limit to their discretion.
Keywords: E44; G28; H7; 330; Credit and credit aggregates; Financial stability; Financial systems regulation and policies; Regional economic developments